GPR15-guided CD8+ T regulatory cells control intestinal inflammation - Jing Cui; Zuojia Chen; Yan H. Cheng; Jia Nie; Maria H. Zhu; Chen Xiang; Samuel Chauvin; Wiem Lassoued; Can Liu; Kartika Padhan; Jian Song; Joy A. Pai; et al. (Nature, 2026)
Abstract Inflammatory bowel disease (IBD) causes chronic suffering from gastrointestinal inflammation and dysfunction that can progress to colon cancer 1,2 . The prevalence of the disease is increasing, and there is an urgent need to better understand its pathogenic mechanisms to improve treatment. We show that GPR15—a G-protein-coupled receptor expressed in immune cells and described previously as an entry co-factor for human and simian immunodeficiency viruses 3 —is a marker and homing receptor for a subset of intramucosal GPR15-guided regulatory CD8 + T lymphocytes (CD8 + T IGR cells). Deleterious GPR15 gene variants in humans cause defective homing of CD8 + T IGR cells and are associated with severe early-onset IBD. Moreover, CD8 + T IGR cells are reduced in the intestinal mucosa of individuals with sporadic IBD. In mice, GPR15 deficiency impairs colonic homing of CD8 + T IGR cells, leading to accumulation of inflammatory macrophages and increased susceptibility to colitis. CD8 + T IGR cells potently kill macrophages activated by intestinal damage or disease using Fas ligand and TNF-related weak inducer of apoptosis (TWEAK). The identification of CD8 + T IGR cells yields new insights into organ-specific immune regulation and potential therapeutics for IBD.